The role of breathing techniques in the management of asthma: a systematic review - Zafar, Syeda Nabiha; Maliha Khalid; Ayesha Jamil; Sara Khawar Butt; Aneeqa Manzoor; Mishal Nadeem (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the effectiveness of breathing techniques in the management of asthma. Method: The systematic review was conducted from July 2021 to August 2022, and comprised search on PubMed, Google Scholar, and MEDLINE databases using the population-intervention-control-outcomes format and Boolean operators. Relevant randomised controlled trials published in the English language in the preceding 10 years were included. The last literature search was done on January 15, 2022. To evaluate the bias in studies, the Cochrane risk of bias tool was used. PEDro scale was used to assess the quality of the trials analysed. Results: Of the 250 studies initially identified, 11(4.4%) random controlled trials were analysed in detail. The quality of methodology was high, and the studies reported significant improvement with the use of breathing techniques in symptoms of asthma and quality of life along with a decrease in the use of bronchodilators. Conclusion: Literature supported the use of breathing techniques in the management of asthma. Key Words: Asthma, Breathing technique, Physiotherapy, Quality of life, Symptoms of asthma.